Economic evaluation of a 100% smoke-free law on the hospitality industry in an Argentinean province Evaluación económica sobre las ventas del sector gastronómico después de una ley de ambientes 100% libres de humo en una provincia argentina - Carlos Candioti; Gustavo Rossini; Edith Depetris de Guiguet; Oscar Costa; Verónica Schoj (Instituto Nacional de Salud Pública, 2012)
OBJECTIVES: To assess the economic impact of a 100% smoke-free law on bars and restaurants in an Argentinean province. MATERIALS AND METHODS: We conducted a time series analysis of restaurant and bar revenues in the province of Santa Fe 31 months before and 29 months after the implementation of the 100% smokefree environment law. The neighboring province of Entre Rios without smoking restrictions at the time of this study, was used as the control province. RESULTS: Average taxable revenues post-legislation in the province of Santa Fe as a whole and in the two most important cities were higher when compared to the total provincial revenue pre-legislation. No significant differences were observed with the total revenue from the province of Entre Rios. CONCLUSIONS: We found no statistically significant evidence that the 100% smoke-free environment legislation in the province of Santa Fe, Argentina, had a negative impact on the revenues of local bars and restaurants. OBJETIVOS: Evaluar el impacto económico de una ley de ambientes 100% libres de humo de tabaco sobre las ventas de bares y restaurantes en una provincia argentina. MATERIAL y MÉTODOS: Se realizó un análisis de serie temporal sobre las ventas de bares y restaurantes en Santa Fe, 31 meses antes y 29 meses después de la ley. Se utilizó a la provincia vecina de Entre Ríos, sin ley en el momento del estudio, como provincia control. RESULTADOS: El promedio de ventas post-ley tanto en la provincia de Santa Fe como en sus dos ciudades más importantes fue mayor al compararse con el promedio provincial total pre-ley. No se observaron diferencias significativas en las ventas totales al ser comparadas con la provincia de Entre Ríos. CONCLUSIONES: No se demostró evidencia estadísticamente significativa sobre el impacto negativo de la legislación de ambientes 100% libres de humo sobre las ventas de bares y restaurantes en la provincia de Santa Fe.